The Effect of Budgetary Participation, Organizational Commitment, and Leadership Styles on the Employees’ Performance - Mila Purani Sistiyan; Palikhatun Palikhatun; Payamta Payamta (SEISENSE Journal of Management, 2019)
Aim -This study aimed at gaining the empirical evidence vis-a-vis the effect of budgetary participation, organizational commitment, and leadership styles on the employees’ performance. Design -This study made use of the primary data garnered from questionnaires distributed to the employees who were directly engaged in the preparation of budget within the work units in working area of the state treasury service office (in Indonesian language known by Kantor Pelayanan Perbendaharaan Negara and abbreviated as KPPN) of Surakarta. The work units covered several regions such as Surakarta, Sukoharjo, and Wonogiri. This study incorporated 80 work units under both ministry and institution. Of 165 questionnaires which were distributed, 116 pieces were returned and could further be analyzed. The independent variables in this study fell into budgetary participation, organizational commitment, and leadership styles, whereas the dependent variable was the employees’ performance. Findings -The results indicated the following details: 1) budgetary participation had a positive effect on the employees ‘performance; 2) organizational commitment had a positive effect on the employees’ performance; 3a) the authoritarian leadership style had no effect on the employees’ performance; 3b) the democratic leadership style had a positive effect on the employees’ performance; and 3c) the laissez-faire leadership style had no effect on the employees’ performance.